Protective Effect of Marine Peptide from Netunea arthritica cumingii Against Gentamicin-Induced Hair Cell Damage in Zebrafish - Hongbao Zheng; Ranran Zhu; Yun Zhang; Kechun Liu; Qing Xia; Peihai Li; Xiaoyue Sun; Chen Sun; Shanshan Zhang (Marine Drugs)
Auditory hair cell damage induced by aminoglycoside antibiotics (AmAn) leads to hearing loss, which has a serious effect on people’s mental and physical health. This ototoxicity is thought to be related with the excessive accumulation of reactive oxygen species (ROS) in hair cells. However, therapeutic agents that protect hair cells are limited. Marine peptides have been shown to have excellent potential applications in disease prevention and treatment. Therefore, this study investigated the protective effects of an active peptide from Neptunea arthritica cumingii against AmAn-induced hair cell damage using the model of hair cell damage zebrafish. We identified the number, ultrastructure, and function of hair cells using fluorescence probes and scanning electron microscopy. The uptake of AmAn, ROS level, mitochondrial permeability transition pore, and apoptosis in hair cells were also tested by fluorescence labeling and TUNEL assay. The molecular mechanism for hair cell protection exerted by the peptide was detected by a real-time quantitative PCR assay. The results indicated that the peptide suppressed the uptake of AmAn but did not damage the function of hair cells mediating hearing. It also prevented ROS accumulation, decreased the occurrence of apoptosis, and rescued the abnormal opening and expressions of mitochondrial permeability transition pore and genes related to antioxidants. The peptide may be an effective therapeutic agent for AmAn-induced ototoxicity. In the future, we plan to use mammalian models to further investigate the otoprotective effect of the peptide.